Wage Compensations Due to Risk Aversion and Skewness Affection: German Evidence - Wolfgang Nagl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
As a new approach we study individual wage compensations due to income risksmeasured by the variance and skewness of the wage distributions in different occupational groups. Using German administrative panel data and estimating a fixed effects model we confirm the expected positive effect of the variance and the negative effect ofthe skewness on individual wages.
Keywords: J30; J31; 330; Wage compensation; income risk; Lohnstruktur; Beruf; Einkommen; Risikoaversion; Schätzung; Deutschland